COMPARATIVE PERFORMANCE OF - Nsibande, Charles Muzi (My University, 2011)
The purpose of the research was to determine whether there was any significant difference in the performances of property unit trusts (PUTs) and property loan stocks (PLSs). Since the studies by Fleming (2002) and Kollenberg (2002), a change has been introduced to the legislation governing PUTs, which allows PUTs to leverage up to 30% of their property values. During the last two years, there have been debates about changing the structure of both PUTs and PLSs to resemble the structure of Real Estate Investment Trusts in the United States of America. The study also introduced the application of value at risk (VaR) to compare the return versus risk profile of PUTs against the return versus risk profile of PLSs. The study population was based on all the PUTs and PLSs listed on the JSE Securies Exchange for a period of 15 years. The Sharpe measure was used to determine the performance of the shares over the period 1990 to 2004, first looking at 1-year returns, then 3-year returns, 5-year returns, 7-year returns, 10-year returns and lastly 15-year returns. Both nominal and risk-adjusted returns were subjected to the NCSS statistical program analysis to determine whether there were significant differences. Earlier literature reviewed indicated that the nominal returns would be different but the research findings indicate that there is no significant difference in both nominal and risk-adjusted returns of PUTs compared to the returns of PLSs. However, simple arithmetic analysis, using averages, indicates a difference in the nominal returns, but not in risk-adjusted returns, as expected from the literature review. The VaR analysis clearly indicates that PUTs have better risk-sharing characteristics than PLSs.
MBA - WBS
Keywords: Property unit trusts; Property loan stocks